“Design of Novel MgZrO3@Fe2O3@ZnO as a Core-Shell Nano Catalyst: an Effective Strategy for the Synthesis of Pyranopyrazole Derivatives” - Shelke, Yogita. R.; Bobade, Vivek. D.; Tope, Dipak. R.; Kushare, Sachin. S.; Agashe, Jyoti. A.; Borhade, Ashok. V. (Current Organocatalysis, 2023)
Background: Catalysis has been widely applied in pharmaceutical companies in recent years. This paper reports a useful new approach for the synthesis of pyranopyrazoles. Objectives: One- pot synthesis of pyranopyrazoles using MgZrO 3@Fe 2O 3@ZnO as a novelcore- shell nanocatalyst which increases reaction rate, selectivity, ease of work-up and recyclability of the supports. Method: The present study deals with the synthesis of MgZrO 3@Fe 2O 3@ZnO core-shell catalyst using the sol-gel method. Results: The synthesized MgZrO 3@Fe 2O 3@ZnO core-shell nanoparticles were analysed using XRD, TEM and BET surface area. The nanocatalyst had an average particle size of 20 nm by TEM images and BET Surface area of 58.93 m2/g. Conclusion: Novel MgZrO 3@Fe 2O 3@ZnO core-shell nanoparticles have been used as an efficient and recoverable catalyst for one-pot synthesis of pyranopyrazoles.
Keywords: Reusable catalyst